2008
DOI: 10.1016/j.cdp.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 (PTGS2) gene methylation in epithelial, subepithelial lymphocyte and stromal tissue compartments in a spectrum of esophageal squamous neoplasia

Abstract: Background-Previous studies have shown important effects of stromal elements in carcinogenesis. To explore the tumor-stromal relationship in esophageal neoplasia, we examined methylation of COX-2 (PTGS2), a gene etiologically associated with the development of gastrointestinal cancers, in adjacent foci of epithelium, subepithelial lymphocytes and nonlymphocytic stromal cells found in sections of normal squamous epithelium, squamous dysplasia and invasive esophageal squamous cell carcinoma.Methods-Adjacent foci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These genes are methylated in breast cancer, but are only slightly or not methylated in non-neoplastic breast cancers (120). Gene methylation is a dynamic process in esophageal squamous cancer and cervical cancer; thus, the level of methylation changes with the progression of cancer (121,122). Apart from locally methylated DNA, global gene hypomethylation was confirmed in CAFs of gastric cancer (123).…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…These genes are methylated in breast cancer, but are only slightly or not methylated in non-neoplastic breast cancers (120). Gene methylation is a dynamic process in esophageal squamous cancer and cervical cancer; thus, the level of methylation changes with the progression of cancer (121,122). Apart from locally methylated DNA, global gene hypomethylation was confirmed in CAFs of gastric cancer (123).…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…Here we ask if genome-wide differences in the epigenome underpin the persistent phenotypic differences between CAFs and NPFs. Earlier studies using low-resolution techniques found examples of DNA methylation changes in CAFs or tumor stroma from various cancer types (Hu et al 2005;Fiegl et al 2006;Hanson et al 2006;Rodriguez-Canales et al 2007;Dawsey et al 2008;Jiang et al 2008;Banerjee et al 2014;Vizoso et al 2015). However, the full epigenome landscape of CAFs remains uncharted, so the precise epigenetic changes and their contribution to altered transcriptional patterns is unknown.…”
Section: Australiamentioning
confidence: 99%
“…For each gene, CpG positions were selected based on previously published data (Dawsey et al., ; Madrigano et al., ; Cantone et al., ), as they are more consistent in terms of repeatability of the assay. Four CpG islands were analysed for COX‐2 and TNF‐ α genes while two were assessed for IFN‐ γ gene.…”
Section: Discussionmentioning
confidence: 99%
“…The CpG positions were selected according to data published in literature for the same assessed genes (Dawsey et al., ; Madrigano et al., ; Cantone et al., , which ensures consistency in terms of repeatability of the assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation